2014
DOI: 10.3390/en7074629
|View full text |Cite
|
Sign up to set email alerts
|

Finite Action-Set Learning Automata for Economic Dispatch Considering Electric Vehicles and Renewable Energy Sources

Abstract: Abstract:The coming interaction between a growing electrified vehicle fleet and the desired growth in renewable energy provides new insights into the economic dispatch (ED) problem. This paper presents an economic dispatch model that considers electric vehicle charging, battery exchange stations, and wind farms. This ED model is a high-dimensional, non-linear, and stochastic problem and its solution requires powerful methods. A new finite action-set learning automata (FALA)-based approach that has the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Figure 10 compares the interior noise levels of an electric vehicle (Liiondrive) and a combustion engine vehicle (Fiat 500) at different constant speeds with the noise produced by the vehicle's tyres rolling. It was found that the two cars' interior noise levels were relatively similar at constant speeds, only 1 or 2 dB(A) higher than the rolling noise [21].…”
Section: Comparative Noise Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 10 compares the interior noise levels of an electric vehicle (Liiondrive) and a combustion engine vehicle (Fiat 500) at different constant speeds with the noise produced by the vehicle's tyres rolling. It was found that the two cars' interior noise levels were relatively similar at constant speeds, only 1 or 2 dB(A) higher than the rolling noise [21].…”
Section: Comparative Noise Analysismentioning
confidence: 88%
“…Figure 6 illustrates this point by showing the total noise emissions from the hybrid vehicle's engine and tyres. At 20 km/h, the reduction is more than 3 dB, drops to 1 dB at 50 km/h, and quickly to zero at 50 km/h and above, when tyre noise becomes the dominant factor and the difference in noise emissions between hybrid and non-hybrid cars almost vanishes [19][20][21].…”
Section: Comparative Noise Analysismentioning
confidence: 98%
“…Nunes et al [269] explore the possible complementarities between wind and solar power with EVs charging, the model used is EnergyPLAN. Zhu et al [270] present an economic dispatch model (high-dimensional, non-linear, and stochastic problem and its solution require powerful methods) that considers EV charging, battery stations, and wind farms.…”
Section: Evmentioning
confidence: 99%
“…Statistical information on the mobility patterns and charging behaviors of EVs is usually derived from census data, based on either conventional ICE vehicles or EVs [29,30]. In day-ahead optimal scheduling, optimal schedules of the power flows among EVs and the power grid are determined over a short-term time horizon, of usually 24 h. The expected power demand profiles of EVs are usually computed by applying statistical methods, which take into account probability distributions of the time of arrival and departure of EVs, and the related State Of Charge (SOC) of on-board batteries [31][32][33]. The aim of intraday optimal scheduling is to determine optimal operation plans over short-time periods, of usually few hours.…”
Section: The Smart Charging Conceptmentioning
confidence: 99%